2013
DOI: 10.1007/s11248-013-9723-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping soybean plants transformed with rd29A:AtDREB1A for drought tolerance in the greenhouse and field

Abstract: The development of drought tolerant plants is a high priority because the area suffering from drought is expected to increase in the future due to global warming. One strategy for the development of drought tolerance is to genetically engineer plants with transcription factors (TFs) that regulate the expression of several genes related to abiotic stress defense responses. This work assessed the performance of soybean plants overexpressing the TF DREB1A under drought conditions in the field and in the greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…As mentioned above, these factors can be used to improve drought tolerance in a variety of crops. Our group has utilized these key TFs for the improvement of drought tolerance in crops including rice, wheat, and soybean in collaboration with international and domestic institutes (Pellegrineschi et al, 2004; Hong et al, 2006; Behnam et al, 2007; Bhatnagar-Mathur et al, 2007; Polizel et al, 2011; Datta et al, 2012; Ishizaki et al, 2012; Saint Pierre et al, 2012; Barbosa et al, 2013; Bhatnagar-Mathur et al, 2013; de Paiva Rolla et al, 2013; Engels et al, 2013; Iwaki et al, 2013). Some results using crops including rice and peanut have shown that stress-specific overexpression of DREB1A improves drought tolerance and grain yield compared with controls in the field (Datta et al, 2012; Bhatnagar-Mathur et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, these factors can be used to improve drought tolerance in a variety of crops. Our group has utilized these key TFs for the improvement of drought tolerance in crops including rice, wheat, and soybean in collaboration with international and domestic institutes (Pellegrineschi et al, 2004; Hong et al, 2006; Behnam et al, 2007; Bhatnagar-Mathur et al, 2007; Polizel et al, 2011; Datta et al, 2012; Ishizaki et al, 2012; Saint Pierre et al, 2012; Barbosa et al, 2013; Bhatnagar-Mathur et al, 2013; de Paiva Rolla et al, 2013; Engels et al, 2013; Iwaki et al, 2013). Some results using crops including rice and peanut have shown that stress-specific overexpression of DREB1A improves drought tolerance and grain yield compared with controls in the field (Datta et al, 2012; Bhatnagar-Mathur et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the function of the DREB1/CBF regulon in the regulation of cold stress responses is widely conserved in angiosperms. Overexpression of DREB/CBF TFs has been reported to enhance drought tolerance in transgenic crops including chrysanthemum (Hong et al, 2006), peanut (Bhatnagar-Mathur et al, 2007, Bhatnagar-Mathur et al, 2013), potato (Behnam et al, 2007; Iwaki et al, 2013), rice (Oh et al, 2005; Ito et al, 2006; Datta et al, 2012), soybean (Polizel et al, 2011; de Paiva Rolla et al, 2013), tobacco (Kasuga et al, 2004), tomato (Hsieh et al, 2002a,b), and wheat (Pellegrineschi et al, 2004; Saint Pierre et al, 2012). For example, rice DREB1/CBF-type TFs involved in cold-responsive gene expression also conferred improved tolerance to drought in transgenic rice (Ito et al, 2006).…”
Section: Dreb1/cbf Tfs For Cold-responsive Gene Expression To Improvementioning
confidence: 99%
“…The influence of treatments, namely, drought, diseases, and herbicides on soybean grown in greenhouse have been reported (de Paiva Rolla et al, 2014;Jaidee, Polthanee, & Saenjan, 2012;Lemes et al, 2011;Miles et al, 2008;Twizeyimana et al, 2007). Previous results show that greenhouse conditions have been used for evaluating the response of a treatment on yield of soybean production.…”
Section: Field Vs Greenhouse Metabolic Contentmentioning
confidence: 99%
“…Crops like tomatoes , strawberries (Gündüz & Ozdemir, 2014) (Keyhaninejad, Richins, & O'Connell, 2012) were reported to have improved yield and nutrient content under greenhouse conditions. Whereas in soybeans, the field and greenhouse conditions were studied only for their drought tolerance, disease, and toxicology studies (Dann, Diers, Byrum, & Hammerschmidt, 1998;de Paiva Rolla et al, 2014;Pfleeger, Olszyk, Lee, & Plocher, 2011). However, there is limited research available on understanding changes in the phytochemical content in soybeans grown under greenhouse as compared to the ambient field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Plant genetic engineering provides an important approach for improving drought resistance in crops via the introduction of transgene(s) to mitigate physiological and agronomic penalties associated with drought (Bihmidine et al, 2013; Patel et al, 2015; Mendiondo et al, 2016). One strategy for increasing drought tolerance is to genetically engineer plants with transcription factors (TF) that control the expression of several abiotic stress response genes (Cabello et al, 2014; de Paiva Rolla et al, 2014; Rehman and Mahmood, 2015). TFs, which are important regulators of gene transcription in various organisms, are classified into a number of families based on the sequences and structures of their DNA-binding domains (Lata and Prasad, 2011; Yamasaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%